Developing dendritic cell for SARS-CoV-2 vaccine: Breakthrough in the pandemic - Jonny, Jonny; Putranto, Terawan Agus; Irfon, Raoulian; Sitepu, Enda Cindylosa (Frontiers in Immunology, 2022)
Finding a vaccine that can last a long time and effective against viruses with high mutation rates such as SARS-CoV-2 is still a challenge today. The various vaccines that have been available have decreased in effectiveness and require booster administration. As the professional antigen-presenting cell, Dendritic Cells can also activate the immune system, especially T cells. This ability makes dendritic cells have been developed as vaccines for some types of diseases. In SARS-CoV-2 infection, T cells play a vital role in eliminating the virus, and their presence can be detected in the long term. Hence, this condition shows that the formation of T cell immunity is essential to prevent and control the course of the disease. The construction of vaccines oriented to induce strong T cells response can be formed by utilizing dendritic cells. In this article, we discuss and illustrate the role of dendritic cells and T cells in the pathogenesis of SARS-CoV-2 infection and summarize the crucial role of dendritic cells in the formation of T cell immunity. We arrange the basic concept of developing dendritic cells for SARS-CoV-2 vaccines. A dendritic cell-based vaccine for SARS-CoV-2 has the potential to be an effective vaccine that solves existing problems.